Pengaruh Penambahan Pati Jagung Pada Pembuatan Prototipe Tulang Menggunakan Metode Starch Consolidation - Agung Prabowo; Ahmad Fadli; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hydroxyapatite (HA) is a crystalline molecule composed of phosphorus and calcium. One technique for fabricated porous HA is the starch consolidation method. The objective of this study was to determine the effect of starch addition on porous HA. The study was conducted by mixed HA as much as 20 grams with the amount of starch 8, 10, 12 and 14 grams of corn starch, and 25 ml of distilled water to form a slurry. The slurry formed is then stirred at 400 rpm. The mixture is then poured into a mould. Then the mixture in the mould was heated to 100oC for 60 minutes. After that, the green bodies are removed from the mould and dried in an oven at 80°C for 24 hours and 110°C for 8 hours. The dried sample is then put into the furnace. Combustion is carried out at a temperature of 600˚C and ended with sintering at a temperature of 1250˚C each for 1 hour. Increasing the addition of starch causes the greater of the shrinkage and porosity, and the density and bending strength is getting smaller. Sintered bodies show shrinkage in the range of 35.47–47.46%, porosity 22.0-37.75%, density 1.97-2.46 gr / cm3, bending strength 0.33-2.33 MPa and pores size obtained is in the range of 80-150 μm.Keywords: bone replica; hydroxypatite; porosity; starch